Formulation and Evaluation of Polyherbal Capsules for Antidiabetic Activity - SHARMA, AKANKSHA; JAIN, Dr. SOURABH; SHUKLA, DR. KARUNAKAR (International Journal of Multidisciplinary Research and Studies, 2020)
Azadirachta indica (Neem), Tinospora cordifolia (Guduchi), Andrographis paniculata (Kalmegh), Moringa oleifera (Surjana), Momordica charantia (Karela) are well-known plants available throughout India and they are commonly used for the treatment of various diseases including diabetes mellitus. The antidiabetic activity of the individual plant parts is well known, but the synergistic or combined effects are unclear. The concept of polyherbalism has been highlighted in Sharangdhar Samhita, an Ayurvedic literature dating back to 1300 AD. Polyherbal formulations enhance the therapeutic action and reduce the concentrations of single herbs, thereby reducing adverse events. The aim of the present study was to evaluate physicochemical, phytochemical analysis of individual herbs, to formulate and evaluate capsule polyherbal formulation of aqueous extract and evaluate its antidiabetic potential. The physicochemical evaluations carried out in terms of foreign organic matter, moisture content, ash value, swelling index, extractive value. Qualitative analysis of various phytochemical constituents was determined by the well-known test protocol available in the literature. The polyherbal formulation contains the aqueous extracts of Neem, Guduchi, Kalmegh, Surjana and Karela. The quality of the finished product was evaluated as per the World Health Organization's guidelines for the quality control of herbal materials. The quality testing parameters of the polyherbal formulation were within the limits. α- Amylase inhibition activity of polyherbal formulation was studied. The results of the work indicate that the selected plants possessed considerable invitro anti diabetic activity and further these effects need to be confirmed using in vivo models for its effective utilization as therapeutic agents.